The Application of Mask Diplomacy: Chinaâ€™s Belt and Road Initiative as Health Diplomacy in Middle East and North Africa (MENA) Countries During COVID-19 - Titing Reza Fahrisa; Siti Rokhmawati Susanto; Renatha Rossdiana; Abraham Pardamean (Universitas Airlangga, 2023)
Chinaâ€™s Belt and Road Initiative (BRI) is a diversification of economic, diplomatic, and geopolitical activities, previously known as the â€œNew Silk Roadâ€, which was later changed to â€œOne Belt and One Roadâ€. BRI is one of the Chinese Governmentâ€™s most ambitious foreign and economic policies. China uses this route to expand its influence and gain attention in destinations in commodities, energy, transportation, and others in the Middle East & North Africa (MENA) countries. This paper uses descriptive qualitative methods to explore various unique phenomena from the Health Silk Road against Vaccination in MENA countries. As a result, 17 countries have become members of the BRI and have cooperated with China, and at this time of the COVID-19 pandemic crisis, most MENA countries are using vaccine diplomacy from China to overcome their crisis. This situation is used for China to carry out â€œMask Diplomacyâ€ to expand its influence in MENA countries. This proves to be effective for China in improving and creating more significant opportunities to emerge as a â€œheroâ€ in providing health services to developing countries while increasing its presence in the world. Kata Kunci: COVID-19; Vaccine diplomacy; Belt Road Initiative; Mask Diplomacy; MENA